Management of Uterine Inversion Due to Endometrial Adenocarcinoma: A Case Report - Sansan Rodrigue SIB; ZAMANE, Hyacinthe; KOMBOIGO, Evelyne; OUEDRAOGO, Issa; TARNAGADA, Dolain Alexandre; SANOGO, Moussa; SAWADOGO, Yobi Alexis; KIEMTORE, Sibraogo; OUEDRAOGO, Ali (HEALTH RESEARCH IN AFRICA, 2024)
RÉSUMÉ Introduction. L'inversion utérine se produit lorsque le sommet de l'utérus s'affaisse vers l'intérieur et descend dans la cavité utérine, voire ressort à travers le col de l'utérus et dans le vagin. Observation. Nous rapportons un cas lié à un adénocarcinome de l’endomètre chez une patiente de 65 ans, admise pour des métrorragies. A l’admission, la présence d’une masse intravaginale a fait suspecter un cancer du col. Plus tard l’extériorisation de la masse a permis d’identifier une tumeur endométriale compliquée d’inversion utérine. Une hystérectomie et une annexectomie bilatérale ont été réalisées avec un abord vaginal et abdominal. Les suites ont été simples et l’examen anatomopathologique de la pièce opératoire a révélé un adénocarcinome de l’endomètre. Conclusion. Une sensibilisation des populations pour qu’elles consultent à temps devant les signes d’appel de tumeurs endo-utérines serait utile. ABSTRACT Introduction. Uterine inversion occurs when the top of the uterus collapses inward and descends into the uterine cavity or even protrudes through the cervix and into the vagina. Observation. We report a case related to endometrial adenocarcinoma in a 65-year-old patient admitted for metrorrhagia. Upon admission, the presence of an intravaginal mass raised suspicion of cervical cancer. Later, the externalization of the mass allowed identification of an endometrial tumor complicated by uterine inversion. A hysterectomy with bilateral annexectomy was performed through vaginal and abdominal approaches. The postoperative course was uneventful and pathological examination of the specimen revealed endometrial adenocarcinoma. Conclusion. Raising awareness among the population to seek timely medical attention when presenting with signs of endo-uterine tumors would be beneficial.